The Burden of Unanticipated Government Spending - Burkhard Heer; Christian Scharrer (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study the impact of a government spending shock on the distribution of income and wealth between cohorts in a dynamic stochastic Overlapping Generations model with two types of households, Ricardian households and rule-of-thumb consumers. We demonstrate that an unexpected increase in government spending increases income inequality and decreases wealth inequality. In contrast to the conventional wisdom that the financing of additional expenditures by debt rather than taxes especially burdens young generations, we find that a debt-financed increase in government spending also harms Ricardian households during retirement, while workers close to retirement benefit. The crucial element in our analysis is a wealth effect that results from the decline in the price of capital due to higher government debt.
Keywords: E62; E30; E12; E24; D31; 330; fiscal policy; debt financing; income and wealth distribution; rule-of-thumb consumers; Ricardian households; overlapping generations